An Overview of Marriage Status Using Fake Divorce Certificates: Tinjauan Status Pernikahan Menggunakan Akta Cerai Palsu - Sifani Ekawati; Sri Budi Purwaningsih; Emy Rosnawati (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the legal consequences if a marriage is carried out using a fake divorce certificate. And also And also to find out the legal sanctions imposed on someone who is getting married by using a fake divorce certificate. The method used is normatife juridicl with a statutory approach. Marriage using a fake divorce certificate does not only cover the area of civil law but also criminal law, which imposes sanctions on the perpetrator and the party who participates in the forgery. The conclusion from this research is that marital status using a fake divorce certificate can be canceled. Then the parties have their status as before the marriage. And parties involved in committing the crime of counterfeiting are punished by up to eight years in prison